2017
DOI: 10.5415/apallergy.2017.7.3.156
|View full text |Cite
|
Sign up to set email alerts
|

Self-report prevalence and associated factors to drug hypersensitivity in Mexican young adults

Abstract: BackgroundDrug hypersensitivity is defined as any unfavorable reaction that occurs after the administration of any drug. It may or may not be mediated by the involvement of the immune system. Epidemiological data related to drug hypersensitivity reactions in our country are scarce.ObjectiveTo determine the prevalence of drug hypersensitivity in a group of young adults, as well as to identify associated factors.MethodsA structured questionnaire was applied to young people aged 18 to 25 years. The instrument was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…19 Previous studies showed that antimicrobials induced hypersensitivity reactions are in high prevalence. [20][21][22][23][24][25] Also worrisome is the finding that 13% were undecided and 26% of respondents agreed that pregnant women and breastfeeding women should not use any antimicrobials. Antimicrobial treatment of infections is important for the health of women and their children during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Previous studies showed that antimicrobials induced hypersensitivity reactions are in high prevalence. [20][21][22][23][24][25] Also worrisome is the finding that 13% were undecided and 26% of respondents agreed that pregnant women and breastfeeding women should not use any antimicrobials. Antimicrobial treatment of infections is important for the health of women and their children during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects are common in treatment with antibiotics . Previous studies showed that antimicrobials induced hypersensitivity reactions are in high prevalence . Also worrisome is the finding that 13% were undecided and 26% of respondents agreed that pregnant women and breastfeeding women should not use any antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we found a significant association between a personal history of asthma and prevalence of DHR. Multiple studies conducted around the world, including Mexico, support the hypothesis that allergic conditions are a risk factor for drug hypersensitivity [1,3,5,6].…”
mentioning
confidence: 97%
“…Epidemiological studies have shown that more than 5% of the population have experienced a DHR at some point in their lives [1][2][3]. For many years, antibiotics have been the main culprits, followed by nonsteroidal anti-inflammatory drugs (NSAIDs).…”
mentioning
confidence: 99%
See 1 more Smart Citation